A new futuristic glaucoma therapeutic management paradigm - Gehlot, Anusuya; Raichandni, Surbhi; Trehan, Neeta; Dua, Mitali; Singh, Jitendra; Gehlot, Bhavya (International Journal of Basic & Clinical Pharmacology, 2017)
Glaucoma is a group of diseases, characterized by a progressive form of optic nerve damage. Current studies indicate more selective pathophysiological involvement, thereby targeted therapies are warranted. Although both the prostaglandin analogs and beta blockers are still, most commonly used drugs for glaucoma, due to their efficacy, lack of adverse effects. In addition, a stepped care approach is the corner stone for its management. In addition, attempts have been made to enhance patient compliance and ocular delivery of already available anti-glaucoma drugs such as pilocarpine and timolol maleate. Notable among futuristic treatment options are; novel delivery systems, benzalkonium chloride-free drugs, various glaucoma drainage devices, new targeted therapies and prompt diagnosis plus aggressive treatment, in patients with primary angle closure glaucoma. Promising new focus on vision sparing, greater patient safety and tolerability will provide improved treatment options and long-term preservation of vision and quality of life.